2006
DOI: 10.1111/j.1365-2893.2006.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF‐alpha promoter polymorphisms with the outcomes of hepatitis B virus infection in Chinese Han population

Abstract: Host genetic factors and environment factors including hepatitis B virus (HBV) genotypes are widely studied for the different outcomes of HBV infection. Recent studies suggest that tumour necrosis factor-alpha (TNF-alpha) plays a pivotal role in the viral clearance and host immune response to HBV, and the capacity for TNF-alpha production in individuals is influenced by a major genetic component. In this study, we aimed to explore whether the single-nucleotide polymorphisms (SNPs) of TNF-alpha promoter are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 29 publications
2
42
2
1
Order By: Relevance
“…There have been many reports on the association of TNF-α-308, -238, and -863 with different diseases, such as hepatitis B virus infection (Du et al, 2006;Basturk et al, 2008) and breast cancer (Yang et al, 2011). In our study, we combined the three SNPs and the haplotype association analysis of TNF-α SNPs (-308/-238/-863) showed that the TNF-α AGA haplotype was present at a higher frequency in the OA-TB patients (12.1%) than in the healthy volunteers (3.5%), indicating that it was a risk factor for OA-TB (OR = 4.201, 95%CI = 1.80-9.91, P = 0.010).…”
Section: Discusssionmentioning
confidence: 99%
“…There have been many reports on the association of TNF-α-308, -238, and -863 with different diseases, such as hepatitis B virus infection (Du et al, 2006;Basturk et al, 2008) and breast cancer (Yang et al, 2011). In our study, we combined the three SNPs and the haplotype association analysis of TNF-α SNPs (-308/-238/-863) showed that the TNF-α AGA haplotype was present at a higher frequency in the OA-TB patients (12.1%) than in the healthy volunteers (3.5%), indicating that it was a risk factor for OA-TB (OR = 4.201, 95%CI = 1.80-9.91, P = 0.010).…”
Section: Discusssionmentioning
confidence: 99%
“…The base replacement of G to A at site -308 leads to sequence variants in its promoter region. Several studies have reported conflicting results regarding the effect of the TNF-α-308 sequence variants on chronic hepatitis B (CHB) viral infections (Höhler et al, 1998;Du et al, 2006;Basturk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The important biological effects of TNF-α and the location of TNF-α (within a region of chromosome 6) have prompted studies on the relationship between TNF-α polymorphisms and diseases. Studies have found that the TNF-α-238A/G polymorphism is closely associated with many autoimmune diseases, such as Hepatitis B [15], SLE [16], coronary heart disease complicated with diabetes mellitus [17], and aplastic anemia [18]. TNF-α-238A is the disease susceptibility allele and -238G is the protective allele.…”
Section: Discussionmentioning
confidence: 99%